A rare case of multiple phosphaturic mesenchymal tumors along a tendon sheath inducing osteomalacia. Issue 1 (December 2017) - Arai, Ryuta; Onodera, Tomohiro; Terkawi, Mohamad; Mitsuhashi, Tomoko; Kondo, Eiji; Iwasaki, Norimasa
Abstract Background Tumor-induced osteomalacia (TIO) is a rare paraneoplastic syndrome characterized by renal phosphate wasting, hypophosphatemia, reduction of 1, 25-dihydroxyl vitamin D, and bone calcification disorders. Tumors associated with TIO are typically phosphaturic mesenchymal tumors that are bone and soft tissue origin and often present as a solitary tumor. The high production of fibroblast growth factor 23 (FGF23) by the tumor is believed to be the causative factor responsible for the impaired renal tubular phosphate reabsorption, hypophosphatemia and osteomalacia. Complete removal of the tumors by surgery is the most effective procedure for treatment. Identification of the tumors by advanced imaging techniques is difficult because TIO is small and exist within bone and soft tissue. However, systemic venous sampling has been frequently reported to be useful for diagnosing TIO patients. Case presentation We experienced a case of 39-year-old male with diffuse bone pain and multiple fragility fractures caused by multiple FGF23-secreting tumors found in the hallux. Laboratory testing showed hypophosphatemia due to renal phosphate wasting and high levels of serum FGF23. Contrast-enhanced MRI showed three soft tissue tumors and an intraosseous tumor located in the right hallux. Systemic venous sampling of FGF23 revealed an elevation in the right common iliac vein and external iliac vein, which suggested that the tumors in the right hallux were responsible for overproduction of FGF23. Thereafter, these tumors were surgically removed and subjected to histopathological examinations. The three soft tissue tumors were diagnosed as phosphaturic mesenchymal tumors, which are known to be responsible for TIO. The fourth tumor had no tumor structure and was consisting of hyaline cartilage and bone tissue. Immediately after surgery, we noted a sharply decrease in serum level of FGF23, associated with an improved hypophosphatemia and a gradual relief of systematic pain that disappeared within two months of surgery. Conclusion The authors reported an unusual case of osteomalacia induced by multiple phosphaturic mesenchymal tumors located in the hallux. Definition of tumors localization by systemic venous sampling led to successful treatment and cure this patient. The presence of osteochondral tissues in the intraosseous tumor might be developed from undifferentiated mesenchymal cells due to high level of FGF23 produced by phosphaturic mesenchymal tumors.